2019
DOI: 10.1073/pnas.1908736116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple male reproductive tract-specific proteins that regulate sperm migration through the oviduct in mice

Abstract: CRISPR/Cas9-mediated genome editing technology enables researchers to efficiently generate and analyze genetically modified animals. We have taken advantage of this game-changing technology to uncover essential factors for fertility. In this study, we generated knockouts (KOs) of multiple male reproductive organ-specific genes and performed phenotypic screening of these null mutant mice to attempt to identify proteins essential for male fertility. We focused on making large deletions (dels) within 2 gene clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 55 publications
(93 reference statements)
1
52
0
Order By: Relevance
“…Since Spint4/5 null male mice are severely subfertile, without an apparent difference in epididymis histology, sperm number, sperm morphology, and sperm motility parameters in comparison to the wild-type (WT) mice, this phenocopies the reproductive phenotype of several null mice of testis-, epididymis-, or prostate-specific genes (Sof1, Tmem95, and Spaca6; Pate8, and Pate10), which reveal a requirement in regulating sperm migration through the oviduct and sperm-oocyte fusion in mice [92,93]. A severe fertility defect associated with normal sperm number, morphology, and motility is also shared among mice lacking the sperm membrane protein ADAM3, thought to be crucial in sperm-ZP binding and sperm migration through the uterotubular junction (UTJ) [94,95].…”
Section: Drug Target Specificity Of Novel Targetsmentioning
confidence: 78%
“…Since Spint4/5 null male mice are severely subfertile, without an apparent difference in epididymis histology, sperm number, sperm morphology, and sperm motility parameters in comparison to the wild-type (WT) mice, this phenocopies the reproductive phenotype of several null mice of testis-, epididymis-, or prostate-specific genes (Sof1, Tmem95, and Spaca6; Pate8, and Pate10), which reveal a requirement in regulating sperm migration through the oviduct and sperm-oocyte fusion in mice [92,93]. A severe fertility defect associated with normal sperm number, morphology, and motility is also shared among mice lacking the sperm membrane protein ADAM3, thought to be crucial in sperm-ZP binding and sperm migration through the uterotubular junction (UTJ) [94,95].…”
Section: Drug Target Specificity Of Novel Targetsmentioning
confidence: 78%
“…The CRISPR-KO approach efficiently screens male fertility genes in vivo. In fact, we revealed that more than 90 genes are dispensable (22)(23)(24)(25)(26), while 10 genes and two clusters are required (21,(27)(28)(29)(30) for male fertility. Recently, we reported that a testis-specific gene, 4930451I11Rik (renamed as Fertilization Influencing Membrane Protein [Fimp]), is another sperm factor critical for sperm−oocyte fusion (31).…”
mentioning
confidence: 91%
“…Due to the power of the CRISPR/Cas9 system, we have the ability to efficiently and accurately delete family cluster genes. While the Oosp family was not found to be critical for fertility, we have identified multiple male reproductive tract specific family cluster proteins that are [41]. The PATE and CST families are crucial for male fertility [41].…”
Section: Discussionmentioning
confidence: 75%
“…While the Oosp family was not found to be critical for fertility, we have identified multiple male reproductive tract specific family cluster proteins that are [41]. The PATE and CST families are crucial for male fertility [41]. Interestingly, a few of these genes were not essential individually but rendered the male mice to be infertile when knocked out together.…”
Section: Discussionmentioning
confidence: 86%